Evaluation of the Relationship Between Placental Thickness and Obstetric Doppler Parameters During the Second Trimester - Emine Aydin; Ayca Nazli Bulut (Medical Network, 2020)
OBJECTIVE: To determine whether there is a relationship between placental thickness and the umbilical artery and uterine artery Doppler evaluation in the second trimester. STUDY DESIGN: The placental thickness and the umbilical artery and uterine artery Doppler evaluations were recorded by a single operator for patients who were admitted for an obstetric follow-up or fetal anatomy screening at 18-28 gestational weeks. The relation between these variables was investigated by evaluating the patients only once. RESULTS: In our study, the mean placental thickness was 31.7 (SD±8.01) mm. The umbilical artery Doppler parameters did not correlate with the placental thickness. The uterine artery Doppler systolic/diastolic velocity, Pulsatility index and Resistance index values positively correlated with the placental thickness. However, these correlations were not statistically significant. CONCLUSIONS: Although there was no relationship between the placental thickness and obstetric Doppler parameters in this study, we suggest that they are likely important factors and their significance should be evaluated in future studies